Effectiveness of betel and kaffir lime combination form of leaf infusion as an in-vitro antiseptic candidate - Budiarti, Lia Yulia; Isnaini; Nurzahida, Gusti Nadya; Derlin, Ellanda Permata; Fahmi, Yafi; Fahdyanoor (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: Natural antiseptics can be alternatives to reduce the adverse effects of alcohol. An antiseptic is classified as effective if it has an inhibitory ability and a phenol coefficient value ≥ 1. Betel plants (Piper betle L.) and kaffir lime (Citrus hystrix DC.) contain a variety of antibacterial compounds and have the potential to act as an antiseptic.Objective: To analyze the in vitro effectiveness of a combined leaf infusion preparation of betel (PB) and kaffir lime (CH) as potential antiseptic candidates.Methods: This quasi-experimental research employed a post-test-only control group design. We utilized diffusion (measuring inhibition zone) and dilution (determining phenol coefficients) methods. The treatments, performed in triplicate, included PB+CH infusion at concentrations 6.25%, 12.5%, 25%, 50%, 75%, and 100%, with 70% alcohol and 5% phenol as control. They were tested against five types of ATCC standard bacterial isolates.Results: Phytochemical screening of the tested infusion revealed the presence of phenolic compounds, flavonoids, alkaloids, tannins, saponins, and terpenoids. The inhibition zone area increased with concentration, with PB+CH 100% producing the most significant effect. ANOVA and post-hoc Duncan test analysis (p < 0.05) showed significant differences between treatment groups. PB+CH infusion at 75-100% produced antibacterial effects exceeding the control for all bacteria tested, except S. typhi. Phenol coefficient tests (dilution 1:20-1:250) showed the effectiveness of PB+CH infusion as a potential antiseptic. The infusion had a phenol equivalent coefficient of 5% against S. aureus, S. epidermidis, E. coli, and P. aeruginosa but only 0.99 ± 0.07 for S. typhi. The 70% alcohol coefficient value was < 1. Conclusion: The combined infusion of betel leaves and kaffir lime demonstrates significant antibacterial activity and shows a potential candidate as an effective natural antiseptic.